A Computed Tomography Angiography (CTA): Based score (SGPGI score) to predict level of difficulty, operative, and postoperative outcomes for right-sided radical nephrectomy. Issue 3 (August 2022) - Singh, Uday P; Madhavan, Kumar; Yadav, Priyank; Soni, Rahul; Lal, Hira; Sureka, Sanjoy K; Kapoor, Rakesh; Srivastava, Aneesh
Objective: With the advent of laparoscopic approach for the large (T1b–T3a ± N1) right renal masses, higher rates of complications and conversion to open surgery are being reported. The role of preoperative angioembolization (PAE), which has increased cost and inherent morbidity but may help in select circumstances has also not been clearly defined in the literature. We therefore devised a scoring system (SGPGI score) based on pre-operative Computed Tomography Angiography (CTA) to predict the level of difficulty of radical nephrectomy and enhance its safety and efficacy which could also be used for the judicious use of PAE in selected cases. Methods: In a prospective observational study on 52 patients with right renal masses from January 2014 to July 2018, we calculated a score based on CTA parameters. The patients were stratified for type and duration of surgery, blood loss, postoperative stay, and Clavien-Dindo grade of postoperative complications. Results: Patients were classified into three groups based on our scoring system. Progressively groups with higher score had higher blood loss, operating time, complications and hospital stay, and were more likely to have undergone conversion to open surgery (Area under curve 0.8625 for a cut off score of 10). Intraclass Correlation Coefficient (ICC) was 0.678–1 for the different components of our score. Conclusion: The pre-operative CTA based SGPGI score evaluates right renal masses and is able to predict intra-operative difficulties effectively, leading to enhancement of surgery safety and efficacy. It also helps judiciously use PAE.